The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/bcp.14315
|View full text |Cite
|
Sign up to set email alerts
|

Effects of single green tea ingestion on pharmacokinetics of nadolol in healthy volunteers

Abstract: The aim of this study was to investigate the effects of a single green tea (GT), administered concomitantly or 1 hour before nadolol intake on nadolol pharmacokinetics. Methods: In a randomized 3-phase crossover study, 11 healthy volunteers received an oral administration of nadolol with, or 1 hour after preingestion of brewed GT, or with water in a volume of 150 mL. Results: Geometric mean ratio with 90% confidence interval for nadolol AUC 0-48 was 0.371 (0.303-0.439) with concomitant GT. In addition, ingesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 17 publications
(47 reference statements)
0
19
0
Order By: Relevance
“…EGCG and other catechins have been reported to inhibit drug metabolism enzymes and transporters, such as cytochrome P450 (CYP), organic anion transporting polypeptides (OATPs), and P‐glycoprotein 8–12 . Moreover, previous studies by our group have demonstrated that green tea and EGCG‐concentrated green tea extract (GTE) significantly reduced plasma concentrations of a hydrophilic β‐blocker, nadolol, in humans, probably by inhibiting the intestinal absorption of nadolol 12–14 . These findings pose a hypothesis that the pharmacokinetics of hydrophilic cardiovascular drugs could be susceptible to green tea consumption.…”
Section: Methodsmentioning
confidence: 84%
See 3 more Smart Citations
“…EGCG and other catechins have been reported to inhibit drug metabolism enzymes and transporters, such as cytochrome P450 (CYP), organic anion transporting polypeptides (OATPs), and P‐glycoprotein 8–12 . Moreover, previous studies by our group have demonstrated that green tea and EGCG‐concentrated green tea extract (GTE) significantly reduced plasma concentrations of a hydrophilic β‐blocker, nadolol, in humans, probably by inhibiting the intestinal absorption of nadolol 12–14 . These findings pose a hypothesis that the pharmacokinetics of hydrophilic cardiovascular drugs could be susceptible to green tea consumption.…”
Section: Methodsmentioning
confidence: 84%
“…[8][9][10][11][12] Moreover, previous studies by our group have demonstrated that green tea and EGCGconcentrated green tea extract (GTE) significantly reduced plasma concentrations of a hydrophilic β-blocker, nadolol, in humans, probably by inhibiting the intestinal absorption of nadolol. [12][13][14] These findings pose a hypothesis that the pharmacokinetics of hydrophilic cardiovascular drugs could be susceptible to green tea consumption.…”
Section: Lisinopril-green Tea Interactionmentioning
confidence: 85%
See 2 more Smart Citations
“…For this study, we reanalyzed the pharmacokinetic data of nadolol from 4 previously conducted studies in healthy Japanese volunteers. 11,13,18,19 The studies were registered in the UMIN Clinical Trials Registry under the code numbers UMIN000004221, UMIN000006064, UMIN000019398, and UMIN00 0019761. The study protocols were approved by the ethics committee of Fukushima Medical University.…”
Section: Clinical Datamentioning
confidence: 99%